Blending learning – from niche to norm. Issue 2 (3rd April 2021) - Ní Uigín, Dorothy; Cofaigh, Éamon Ó.
Abstract : Blended Learning has existed for many years, and while it has gradually been gaining a measure of impetus in third-level programmes, it has traditionally been used as a cost-effective way to deliver part-time courses to adult learners. Delivered at times that are usually considered outside of core teaching hours (evening classes and weekend workshops), blended-learning programmes have often been delivered by part-time staff or research students rather than being embraced by the permanent lecturers. With the onset of the Covid-19 pandemic, several programmes were redesigned to adopt a blend of online and on-campus teaching. While not officially defined as blended-learning programmes, this mode of learning has been incorporated across the teaching spectrum by lecturers who, in some cases, have little to no knowledge or experience of it. This has brought several challenges not only to teachers, but also to students who very often may not be as tech-savvy as they claim to be. These challenges notwithstanding, it is important to consider this online migration, not as a stopgap process, engendered out of necessity, but rather as an importunity to embrace certain approaches that may have previously seemed daunting. The advantages of blended or online learning that teachers have been using this academic year must not be abandoned when no longer needed, but rather incorporated into teaching programmes as integral components of a more holistic learning experience. This article provides a brief overview of how some more mainstream programmes adapted their content to cater to a new learning environment. The blended-learning tools and functionalities incorporated into this teaching will be examined, firstly in how they formed an integral part of blended-learning modules and how they have been adjusted to target a fulltime student audience. Finally, and perhaps most crucially, as we move to a post-Covid environment, suggestions are made regarding how certain aspects of blended learning can be retained when returning to a 'normal' classroom.